EFFECT OF ANTI-VEGF THERAPY ON THE STRUCTURAL STATE OF THE RETINA IN DIABETIC MACULAR EDEMA - M. M. Bikbov; R. R. Fayzrakhmanov; R. M. Zaynullin (Acta Biomedica Scientifica, 2016)
Objective: to analyze the structural state of the central area of the retina in diabetic macular edema in the background anti-VEGF therapy. Methods. The study included 38 patients (40 eyes) with diabetic macular edema. All patients received anti-VEGF-ranibizumab therapy at a dose of 0.05 ml. The results were analyzed after three intravitreal injections with 1 month interval. We assessed visual acuity, morphological and anatomical structure of the macular area, the sensitivity of the retina and macular pigment optical density Results. Analyzing optical density of the macular pigment we revealed a significant increase of all parameters in 73 % of patients after the therapy. The average value of the optical density before treatment was at 0.102 ± 0.01 du, on the background of anti-VEGF-therapy this figure went up to 0.213 ± 0.01 (p < 0.05). According to the optical coherence tomography average retinal thickness before treatment made 404.62 ± 15.23 ßm, after the treatment - 300.91 ± 6.43 ßm (р < 0,05). When comparing data of optical coherence tomography and macular pigment optical density we revealed more pronounced decrease in the macular pigment optical density in the area of the retinal edema and a significant increase in the basic parameters on the background of the therapy. Conclusion. Anti-VEGF-therapy significantly improves visual acuity, the recovery profile of macular edema and reduces the zone in patients with diabetic macular edema.